A new Neotropical species of the genus Metriocnemus van der Wulp (Chironomidae: Orthocladiinae) from Eryngium L. (Apiaceae) phytotelmata - Donato, Mariano; Paggi, Analía C. (Zootaxa, 2005)
The larva, pupa, male, and female of a new Neotropical species, Metriocnemus eryngiotelmatus, are described and illustrated. This species was collected from the leaf axils of Eryngium pandanifolium Cham. & Schlecht and E. cabrerae Pontiroli (Apiaceae) in Argentina and Uruguay. Based on characters of the male, the new species is closely related to Metriocnemus costatus Sublette & Sasa.